The Phenomenon of Turnover intention in Production Employees of Fish Processing Factories in Rembang Regency - Rohman Wakhid, Abdur; Ilhami, Susanti Dwi (Journal La Bisecoman, 2024)
The goal of this study is to demonstrate how audit report lag in transportation businesses joined on IDX for the 2020–2022 period is influenced by the company's age, size, financial health, and operational complexity. This research takes a quantitative method. This study's dependent variable is audit report latency, whereas the independent variables are operational complexity, financial health, business size, and age. The population used consists of 15 transportation. The method of gathering data in the research was conducted utilizing the method of purposive sampling. A total of 45 observations from 15 companies make up the research sample. Multiple linear regression is the strategy of data analysis that is used. Based on the test results, it shows that the age of the company and the size of the company partially have a positive but insignificant effect on audit report lag, while the financial condition and operational complexity variables partially have a negative but insignificant effect on audit report lag. The results of this research can be beneficial for the stream of literature related to company age, company size, financial condition, and operational complexity. The results of this research can also be beneficial for companies, where they can take policies regarding financial report management in the timely delivery of financial reports.